Effect of high temperature on nanopores in cokes. (15th February 2023) - Sakurovs, Richard; Grigore, Mihaela; Sokolova, Anna; Mata, Jitendra
Highlights: Coke nanopore numbers increase substantially on heating to 1400 °C and 1600 °C. The greatest increase is observed in the number of 10 nm-radius pores. Above 100 nm size, nearly all newly formed pores are open. Heating at higher temperatures or for longer had greater effects on pore numbers. Abstract: Small Angle Neutron Scattering and Ultra Small Angle Neutron Scattering were used to study the effect of annealing at temperatures of 1400 and 1600 °C, in an inert atmosphere, on the pore size distribution of three cokes prepared from Australian coals. The pore size range investigated was 1 nm to 2 µm. It was found that annealing substantially changed the size distribution of these pores in similar ways for all three cokes examined, despite the difference in rank and maceral composition of the starting coals. The pore sizes at which the greatest percentage changes in numbers occurred on heating was around 10 nm, with an increase in the number of both open and closed pores, by up to a factor of four after annealing at 1600 °C. For pores in the size range 100 nm to 2 µm, the number of closed pores decreased slightly and the number of open pores increased substantially; new open pores were created. The percentage increase in pore numbers introduced by annealing decreased with increasing pore size above 100 nm, but even at 2 µm pore radius, some samples showed a 50 % increase in total pore numbers. Annealing at greater temperature or longer time had a greater effect on pore numbers.